2022
DOI: 10.1007/s00204-022-03434-8
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis decodes transthyretin (TTR) binding and thyroid disrupting effects of per- and polyfluoroalkyl substances (PFAS)

Abstract: Transthyretin (TTR) is a homo-tetramer protein involved in the transport of thyroid hormone (thyroxine; T4) in the plasma and cerebrospinal fluid. Many pollutants have been shown to bind to TTR, which could be alarming as disruption in the thyroid hormone system can lead to several physiological problems. It is also indicated that the monomerization of tetramer and destabilization of monomer can lead to amyloidogenesis. Many compounds are identified that can bind to tetramer and stabilize the tetramer leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…PFASs with a medium chain length and a sulfonate acid group preferentially bind to TTR, while those with chain lengths longer than 12 carbons prefer TBG binding . Some long-chain PFASs, such as PFDoDA, PFUnDA, and perfluorooctanoic acid (PFOA), have been found to strongly interact with blood TTR and show higher toxicity propensity in silico analysis . The binding between PFASs and TTR is driven by hydrogen bonds and hydrophobic interactions, with hydrophobic interactions being the major contributors .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PFASs with a medium chain length and a sulfonate acid group preferentially bind to TTR, while those with chain lengths longer than 12 carbons prefer TBG binding . Some long-chain PFASs, such as PFDoDA, PFUnDA, and perfluorooctanoic acid (PFOA), have been found to strongly interact with blood TTR and show higher toxicity propensity in silico analysis . The binding between PFASs and TTR is driven by hydrogen bonds and hydrophobic interactions, with hydrophobic interactions being the major contributors .…”
Section: Discussionmentioning
confidence: 99%
“…194 The binding between PFASs and TTR is driven by hydrogen bonds and hydrophobic interactions, with hydrophobic interactions being the major contributors. 194 Recent research has also proposed a model to quantitatively evaluate the relationship between TTR-binding chemicals, including PFASs, and FTHs in vivo. The study revealed that the levels of FT4 and FT3 in circulation are affected to different degrees in both general population and individuals with occupational exposure to various TTR-binding chemicals, including hydroxylated PCBs (OH-PCBs), hydroxylated-PBDEs (OH-PBDEs), PFASs, and phenols.…”
Section: Hyperthyroidism Risk Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that several house dust contaminants bind to TTR in a competitive manner with a fluorescent conjugate of T 4 [10]. The bindability of environmental substances to TTR is recognized as a significant issue and potential health hazard [11,12].…”
Section: Introductionmentioning
confidence: 99%